2010
DOI: 10.4314/ajbr.v11i3.50721
|View full text |Cite
|
Sign up to set email alerts
|

Quality of packaged waters sold in ibadan, nigeria

Abstract: The inadequacy of pipe borne water supplies in urban centres is a growing problem. As a result, communities resort to buying water from vendors. In recent years, sachet or bottled water became major sources of drinking water in the households and at work. This study aimed at assessing the chemical and bacteriological quality of packaged water sold in Ibadan, the capital of Oyo State with a population over 3.2 million. A total number of 118 samples of water from several commercial brands sold in the city of Iba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 7 publications
3
36
0
Order By: Relevance
“…However, [10] reported proliferation of bacteria in sachet water in Port Harcourt when stored beyond 4 weeks. In general, the bottle water brands were of better microbial quality compared to sachet water similar to [20] findings that larger proportion of sachet water showed positive coliform counts compared to bottled water sold in Ibadan town. Contamination of packaged drinking water may result from the raw source of water, treatment employed and handling during production.…”
Section: Resultssupporting
confidence: 77%
“…However, [10] reported proliferation of bacteria in sachet water in Port Harcourt when stored beyond 4 weeks. In general, the bottle water brands were of better microbial quality compared to sachet water similar to [20] findings that larger proportion of sachet water showed positive coliform counts compared to bottled water sold in Ibadan town. Contamination of packaged drinking water may result from the raw source of water, treatment employed and handling during production.…”
Section: Resultssupporting
confidence: 77%
“…Microbial evaluation of all water samples revealed high levels of total coliform bacteria in the sachets but not in the bottles. Similar results were found in studies done by Gangil R et al, [11], Majumder AK et al, [31], Semerjian L [10], Urvashi et al, [32], Zeenat et al, [33] and Ajayi AA [34]. The microbial contamination of packaged drinking water could be influenced by factors such as their raw water sources, treatment processes which were employed and hygienic practices which were observed in their productions.…”
Section: Samplingsupporting
confidence: 77%
“…Lack of information on pathogenic bacteria in sachet water on our market creates some uncertainties in our understanding of the overall quality of drinking water on our markets. Ajayi et al (2008) had reported an earlier study of packaged drinking waters in Ibadan, Nigeria in which larger proportions of sachet water were found to show positive coliform counts compared to bottled waters.…”
Section: Discussionmentioning
confidence: 96%